2006
DOI: 10.1124/mol.106.030700
|View full text |Cite
|
Sign up to set email alerts
|

Subunit-Specific Roles of Glycine-Binding Domains in Activation of NR1/NR3 N-Methyl-d-aspartate Receptors

Abstract: N-Methyl-D-aspartate receptors (NMDARs) composed of NR1 and NR3 subunits differ from other NMDAR subtypes in that they require glycine alone for activation. However, little else is known about the activation mechanism of these receptors. Using NMDAR glycine-site agonists/antagonists in conjunction with functional mutagenesis of the NR1 and NR3 ligand-binding cores, we demonstrate quite surprisingly that agonist binding to NR3 alone is sufficient to activate a significant component of NR1/NR3 receptor currents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
102
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(118 citation statements)
references
References 39 publications
12
102
4
Order By: Relevance
“…4, panels B and C and panels E and F). The TK40-mediated potentiation of the glycine-activated current responses and the apparent shift in the bell-shaped concentration-response relationships presumably result from selective inhibition of glycine binding to the GluN1 subunit, which is in agreement with other reports (41,42).…”
Section: Tk40supporting
confidence: 81%
See 3 more Smart Citations
“…4, panels B and C and panels E and F). The TK40-mediated potentiation of the glycine-activated current responses and the apparent shift in the bell-shaped concentration-response relationships presumably result from selective inhibition of glycine binding to the GluN1 subunit, which is in agreement with other reports (41,42).…”
Section: Tk40supporting
confidence: 81%
“…This bellshaped concentration-response relationship is presumably a result of glycine binding to unblocked GluN3 subunits at low glycine concentrations (rising phase). At higher glycine concentrations, the selective block by TK40 at GluN1 subunits is outcompeted, resulting in diminished receptor current (declining phase), which is in agreement with previous reports (41,42). For glycine-activated responses at wild-type GluN1/N3 receptors, we have previously reported that only negligible current responses (Ͻ10 nA) are observed at GluN1/N3A receptors upon glycine application and that glycine concentrations above 10 M result in diminished receptor current at GluN1/N3B receptors, thereby producing a bell-shaped concentration-response relationship (38).…”
Section: Tk40supporting
confidence: 81%
See 2 more Smart Citations
“…The glycine currents produced by these NR1/NR3 receptors are, however, rather small, although assembly and surface insertion occur with similar efficiency as that of conventional NR1/NR2 receptors (13). Recently, antagonists of the NR1 glycine-binding site were found to markedly enhance the glycine responses of NR1/NR3 receptors (13,14), presumably by preventing rapid receptor desensitization caused by glycine binding to the NR1 subunit.An important endogenous modulator of conventional NMDA receptors is the divalent cation Zn 2ϩ , which allosterically inhibits NR1/NR2 receptors in the submicromolar to micromolar concentration range (15-17). Here, we examined whether Zn 2ϩ also affects the glycine-induced currents of heteromeric NR1/NR3A receptors.…”
mentioning
confidence: 99%